(untitled) (Revista Brasileira Multidisciplinar, 2008)
There is still no consensus in the literature about the object and purpose of the accusation of breach of fundamental precept. It is true that the Office should be interpreted in the light of the Constitution and not of the ordinary law. In this sense, it can be an important tool in the defense of fundamental principles considering the originary constitutional rules.